Evaluating adaptation measures for reducing flood risk: A case study in the city of Colombo, Sri Lanka. (July 2019) - Wagenaar, D.J.; Dahm, R.J.; Diermanse, F.L.M.; Dias, W.P.S.; Dissanayake, D.M.S.S.; Vajja, H.P.; Gehrels, J.C.; Bouwer, L.M.
Abstract: Many cities around the world face frequent problems with flooding, which is expected to get worse due to anthropogenic climate change and further urbanization. To tackle these problems often local infrastructural adaptation measures are proposed. In this study a chain of state-of-the-art models is presented that can be used to evaluate the benefits of such measures. Also, a method is presented to calculate the costs of not responding to a changing environment that is slowly aggravating floods. These methods are applied to a case study in the city of Colombo in Sri Lanka. Colombo faces problems with floods that are expected to get worse by further wetland reduction and climate change. Several local measures (infrastructural interventions) are proposed to tackle that problem. This paper shows a method to quantify the expected reduction in future flood damages resulting from the proposed measures, and compares the risk reduction to the proposed measure costs. This is done by creating probabilistic inundation depth maps using a 1D2D hydrodynamic model. A detailed flood damage model and socio-economic development scenarios are then applied to estimate damage with and without the measures. An economic analysis is done to demonstrate the benefits of the measures, which can be used by decision makers. Additionally, calculations are carried out of future flood risk increases when wetland reduction in Colombo continues. In this case, the effect of stopping wetland encroachment is found to be larger than the effect of the structural adaptation measures.